2014
DOI: 10.1007/s00146-014-0560-9
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing care homes with assistive video technology for distributed caregiving

Abstract: Dementia care is becoming increasingly important in Japan as the elderly population grows. Care homes are designed so that caregivers can easily observe and subsequently respond to the needs of people with dementia.However, the layout of care homes can become overly restrictive for residents, for example, by not providing intermediate spaces where people can spontaneously interact and initiate conversations. We present a case study that explores the implementation of video monitoring in two purpose-built care … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 17 publications
2
4
0
Order By: Relevance
“…Staff in other homes were also susceptible to rumours that technologies were being used for this purpose even if not the case. These findings are supported by previous literature ( Niemeijer et al, 2010 , Robinson et al, 2007 , Schikhof et al, 2010 , Sugihara et al, 2015 ) and add to a picture that paints blame as the default response to poor quality health and social care ( Baker, 2015 ). The present study clearly demonstrates that there is a need for greater involvement of staff in discussions about use of monitoring technologies at an early stage of the implementation process to avoid creating a negative culture of an ‘eavesdropping employer’ ( Ciocchetti, 2011 ).…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Staff in other homes were also susceptible to rumours that technologies were being used for this purpose even if not the case. These findings are supported by previous literature ( Niemeijer et al, 2010 , Robinson et al, 2007 , Schikhof et al, 2010 , Sugihara et al, 2015 ) and add to a picture that paints blame as the default response to poor quality health and social care ( Baker, 2015 ). The present study clearly demonstrates that there is a need for greater involvement of staff in discussions about use of monitoring technologies at an early stage of the implementation process to avoid creating a negative culture of an ‘eavesdropping employer’ ( Ciocchetti, 2011 ).…”
Section: Discussionsupporting
confidence: 88%
“…In contrast, the location-based system at Conifer Gardens was beleaguered by false alarms and technical problems, and its full range of data collection capabilities were considered too time-consuming to add value to practice and facilitate successful implementation, particularly when weighed against its financial cost. These findings are supported by the overall picture in the literature which suggests there is a balance between increased confidence, control and coordination in practice delivered by monitoring technologies with overburden from alarms ( Engström et al, 2009 , Niemeijer et al, 2010 , Nijhof et al, 2012 , Sugihara et al, 2015 ). From an ethical perspective, we have discussed above the attractiveness of monitoring technologies for care homes deemed to facilitate fast response to, rather than prevention of, an adverse event.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…In addition to these benefits for residents, it can also help streamline caregiver roles and responsibilities. For example, when Sugihara, Fujinami, Jones, Kadowaki, and Ando () used cameras in the common spaces of a group home for the elderly, caregivers there reported it helped with their work as they needed to check up on people less. However, Sugihara et al () also found that the amount of caregiving time with the cameras did not change; thus, it is possible that this system actually allowed the caregivers to use their time more efficiently by allowing them to just look at the monitors and not requiring physical oversight.…”
Section: Introductionmentioning
confidence: 99%